A STUDY OF THE RELATIONSHIP BETWEEN TEACHERS’ PERCEPTIONS TOWARDS ADMINISTRATIVE SUPPORT AND THEIR COMPETENCE AT NO.1 BASIC EDUCATION HIGH SCHOOL IN HPA-AN TOWNSHIP, KAREN STATE, MYANMAR - NAN MI HNIN LAY; YE, YAN (Scholar: Human Sciences, 2022)
This study aimed to explore teachers’ administrative support perspectives and competence at No. (1) Basic Education High School in Hpa-an, Karen State, Myanmar. The study objectives were (1) To identify teachers’ perceptions towards administrative support, (2) To identify teachers’ perceptions towards their competence (3) To determine the significant relationship between teachers’ perceptions towards administrative support and their competence at the selected school. Two parts of the questionnaire were administrative support, adopted from Methers’ Administrative Support Survey (MASS), 2013, and teacher competence, adopted from Medley’s (1977). Seventy-five full-time teachers were surveyed in this study. The study data were analyzed by frequency, percentage, mean, standard deviation, and Pearson product-moment coefficient. The study findings showed that teachers’ perceptions of administrative support and competence were high. Moreover, the relationship between teachers’ perceptions of administrative support and competence was significant.